2018 White Paper on Recent Issues in Bioanalysis: focus on immunogenicity assays by hybrid LBA/LCMS and regulatory feedback (Part 2 – PK, PD & ADA assays by hybrid LBA/LCMS & regulatory agencies' inputs on bioanalysis, biomarkers and immunogenicity). (29th November 2018) - Neubert, Hendrik; Olah, Timothy; Lee, Anita; Fraser, Stephanie; Dodge, Robert; Laterza, Omar; Szapacs, Matthew; Alley, Stephen C; Saad, Ola M; Amur, Shashi; Chen, Linzhi; Cherry, Elana; et al.
The 2018 12 th Workshop on Recent Issues in Bioanalysis took place in Philadelphia, PA, USA on April 9–13, 2018 with an attendance of over 900 representatives from pharmaceutical/biopharmaceutical companies, biotechnology companies, contract research organizations and regulatory agencies worldwide. WRIB was once again a 5-day, week-long event – a full immersion week of bioanalysis, biomarkers and immunogenicity. As usual, it was specifically designed to facilitate sharing, reviewing, discussing and agreeing on approaches to address the most current issues of interest including both small- and large-molecule bioanalysis involving LCMS, hybrid LBA/LCMS and LBA/cell-based assays approaches. This 2018 White Paper encompasses recommendations emerging from the extensive discussions held during the workshop and is aimed to provide the bioanalytical community with key information and practical solutions on topics and issues addressed, in an effort to enable advances in scientific excellence, improved quality and better regulatory compliance. Due to its length, the 2018 edition of this comprehensive White Paper has been divided into three parts for editorial reasons. This publication (Part 2) covers the recommendations for PK, PD and ADA assays by hybrid LBA/LCMS and regulatory agencies' input. Part 1 (LCMS for small molecules, peptides, oligonucleotides and small molecule biomarkers) and Part 3 (LBA/cell-based assays: immunogenicity, biomarkers and PK assays) are published in volume 10 of Bioanalysis, issues 22 and 24 (2018), respectively.